Livestock Farming of Middle Urals in 1916-2015 - V. N. Mamyachenkov (Научный диалог, 2017)
The attempt is made of historical and economic analysis of the efficiency of the livestock sector of agriculture of the major industrial region of the country under the domination of the administrative command kolkhoz-sovkhoz management system and its adaptation to market conditions. The article is devoted to the subject insufficiently developed in the national historiography, especially in regard to its regional dimension. The study is conducted on materials of two archives of Middle Urals: archive of Territorial body of Federal state statistics service for Sverdlovsk region and the Centre of documentation of public organizations of Sverdlovsk region with the assistance of the scientific and publicistic literature. The relevance of the topic is determined by its high importance for the social sciences, especially history and economy. Scientific novelty of the work is seen in the fact that the new materials discovered by the author in these archives are introduced into scientific usage. It is argued that by the time among the historians and economists there is no consensus concerning the socio-economic potential of the administrative-command system. It is stated that different opinions and assessments in full measure apply to livestock - leading agriculture in most countries. It is declared that regional historians use the topic of agricultural development of livestock breeding in the Sverdlovsk region usually only as auxiliary material in the study of general problems of agriculture complex. It is noted that there are four main stages of development of Middle Urals livestock. It is emphasized that due to the enormous investment in the agricultural sector, the Soviet state for many years was able to create a semblance of efficiency of livestock production. It is proved that economic efficiency is the cornerstone of any socio-economic system. The conclusion is that the restructuring of livestock to a market economy was of a very high price to the agriculture of the Sverdlovsk region.